An anatomical study of the lymph-collecting vessels of the medial thigh and clinical applications of lymphatic vessels preserving profunda femoris artery perforator (LpPAP) flap using pre- and intraoperative indocyanine green (ICG) lymphography. Issue 9 (September 2020) - Karakawa, Ryo; Yoshimatsu, Hidehiko; Tanakura, Kenta; Miyashita, Hiroki; Shibata, Tomoyoshi; Kuramoto, Yukiko; Yano, Tomoyuki
Summary: Background and Objectives: The profunda femoris artery perforator (PAP) flap is gaining popularity in microsurgical reconstruction. The complications that can occur after the PAP flap harvest include donor-site lymphedema, seroma, or cellulitis. The aim of this study was to evaluate and establish a safer technique for the elevation of lymphatic vessels preserving profunda femoris artery perforator (LpPAP) flap using pre- and intraoperative ICG lymphography. In this article, we also evaluate the anatomical relationship between the PAP flap and lymph-collecting vessels. Methods: From July of 2018 to January of 2019, 24 patients with soft tissue defects after tumor resection underwent reconstruction using PAP flaps. The lymph-collecting vessels at the medial thigh area were identified using pre- and intraoperative ICG lymphography. A PAP flap was elevated taking care not to damage lymph-collecting vessels. After flap elevation, the anatomical correlation between lymph-collecting vessels and the anterior edge of the gracilis muscle was measured. The postoperative complications were assessed. Results: PAP flaps survived completely in all cases. In all cases, using intraoperative ICG lymphography, surgeons confirmed that the lymph-collecting vessels in the medial thigh region were left intact. There were no donor site complications such as lymphedema, lymphorrhea, or cellulitis. Conclusion: The elevation technique of an LpPAP flap is effective in reducing the risk of damage to lymph-collecting vessels, and thus reducing chances of postoperative lymphorrhea or iatrogenic lower limb lymphedema.